Effect of COVID-19 on Pregnancy and Neonate’s Vital Parameters: A Systematic Review - Anna Charuta; Monika Smuniewska; Zofia Woźniak; Agnieszka Paziewska (Journal of Pregnancy)
Background. COVID-19 is a new pandemic, which was declared by the World Health Organization in 2019 as a threat to public health. According to numerous reports, it can have negative consequences for pregnant women, labour, and neonates born to infected mothers. The aim of this paper was to gather the evidence and to present a summary of the results of studies concerning COVID-19 in pregnant women and their neonates. Methods. Articles from prestigious journals covering the period from 2020 to February 2023, relevant review papers, and original research articles from PubMed were analysed. In order to analyse the available research literature, the Web of Science, Scopus, and PubMed databases were used, in which the search for articles was conducted using terms (“pregnancy,” “coronavirus,” “SARS-CoV-2,” and “newborn”) and using PRISMA (Preferred Reporting Items for Systemic Reviews and Meta-Analysis) guidelines for clinical trials. Meta-analyses and systematic reviews (2022–2023) on symptoms, neonatal course, and risk of COVID-19 infection have been summarized. Summary of meta-analyses and systematic reviews (2022–2023) on the effect and adverse reaction of the COVID-19 vaccination is presented. Results. As a result of the research conducted, it was confirmed that in most pregnant women, no serious signs of the infection were observed, although isolated cases of death related to COVID-19 in pregnant women were reported. Several authors called attention to the more severe course of the infection in pregnant women with obesity. It seemed that no vertical transmission from mother to child was occurring. Nevertheless, the information was not clinching. The condition of the neonates born to mothers with COVID-19 was in most cases described as normal; however, some papers reported deaths of infected neonates. Conclusions. Due to insufficient data, further research is necessary. Further studies and follow-up are recommended, which would make possible an assessment of remote effects of COVID-19 on pregnancy and vital parameters of the newborn.